Electrospun conductive carbon nanofiber hosts for stable zinc metal anode. (2nd January 2022) - Baek, Sang Ha; Cho, Yoon Jin; Park, Jae Min; Xiong, Peixun; Yeon, Jeong Seok; Rana, Harpalsinh H.; Park, Jeong Hee; Jang, Gun; Lee, Sang Joon; Park, Ho Seok
Summary: Rechargeable zinc metal batteries (RZMBs) are emerging as promising candidates to replace lithium‐ion batteries due to their low cost, safety, and stability under ambient atmosphere. As the conductive substrates lower the actual current density, it is considered a chemical strategy to resolve the dendrite issue of RZMB. Herein, we propose to use the carbon nanofiber as a conductive substrate for the anode of RZMBs, which was prepared via heat treatment of electrospun PAN‐derived nanofiber. Through CV and SEM results performed at a constant current rate of 20 mA cm −2, the optimum amount of zinc deposited on the CNF was determined to be 10 mAh cm −2 . Symmetric cell test for 400 hours showed 60.1% reduction in plating/stripping overpotential when zinc deposited carbon nanofiber was used. This overpotential reduction was attributed to the macroporous structure of ZnCNF and the preferred orientation of zinc to the (002) plane as confirmed by post mortem analyses. RZMB full cells pairing ZnCNF with β‐MnO2 were configured to deliver the 5C‐rate capacity of 106.54 mAh g −1, which was higher 34.13 mAh g −1 with bare zinc. Finally, the long‐term cyclability of ZnCNF|| MnO2 with much lower N/P ratio of 18.0 was confirmed, demonstrating the capacity retention of 89.4%, greater than 73% of bare zinc||MnO2 cell with the N/P ratio of 234.6 over 300 cycles. Abstract : When zinc was deposited on the electrospun carbon nanofibers fabricated by stabilization and carbonization after electrospinning, the actual current density was lowered due to the high surface area of CNF, and as the deposited zinc grew in the (002) direction, a uniform deposition was obtained. This result confirms that carbon nanofiber is a promising conductive substrate for zinc metal anode.